Is There a Motherhood Penalty? Decomposing the Family Wage Gap in Colombia (2013)
The aim of this paper is to provide an estimation and decomposition of the motherhood wage penalty in Colombia. Our empirical strategy was based on the matching procedure designed by Ñopo (The Review of Economics and Statistics, 90(2), 290–299, 2008a) for the case of gender wage gaps. This is an alternative procedure to the well-known Blinder–Oaxaca decomposition method. Using the cross-sectional data of the Colombian Living Standard Survey, the wage gap was decomposed into four components, according to the characteristics of mothers and non-mothers. Three of the components are explained by differences in observable characteristics of women, while the other is the unexplained part of the gap. We found that mothers earn, on average, 1.73 % less than their counterparts without children and that this gap slightly decreased when the group included older women. It is observed from the results that, once schooling was included as a matching variable, the unexplained part of the gap considerably decreased and became non-significant. Thus, we did not find evidence of wage discrimination against mothers in the Colombian labor market.